Biomaterial-assisted anastomotic healing: serosal adhesion of pectin films - Zheng, Yifan; Pierce, Aidan F.; Wagner, Willi Linus; Khalil, Hassan A.; Chen, Zi; Funaya, Charlotta; Ackermann, Maximilian; Mentzer, Steven J. (Polymers, 2021)
Anastomotic leakage is a frequent complication of intestinal surgery and a major source of surgical morbidity. The timing of anastomotic failures suggests that leaks are the result of inadequate mechanical support during the vulnerable phase of wound healing. To identify a biomaterial with physical and mechanical properties appropriate for assisted anastomotic healing, we studied the adhesive properties of the plant-derived structural heteropolysaccharide called pectin. Specifically, we examined high methoxyl citrus pectin films at water contents between 17-24% for their adhesivity to ex vivo porcine small bowel serosa. In assays of tensile adhesion strength, pectin demonstrated significantly greater adhesivity to the serosa than either nanocellulose fiber (NCF) films or pressure sensitive adhesives (PSA) (p < 0.001). Similarly, in assays of shear resistance, pectin demonstrated significantly greater adhesivity to the serosa than either NCF films or PSA (p < 0.001). Finally, the pectin films were capable of effectively sealing linear enterotomies in a bowel simulacrum as well as an ex vivo bowel segment. We conclude that pectin is a biomaterial with physical and adhesive properties capable of facilitating anastomotic healing after intestinal surgery.
Gesehen am 22.10.2021